IMPLEMENTASI DEEP LEARNING DI SEKOLAH DASAR - Puspitasari, Sekar; Jamaludin, Ujang; Rahmani, Anggi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the planning, implementation, and factors supporting and hindering the implementation of deep learning at SDS YPWKS IV in Cilegon. This descriptive qualitative study involved the principal, the vice principal for curriculum, and first-grade teachers as participants. Data were collected through interviews, observations, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The results of the study indicate that deep learning planning is carried out by developing in-depth lesson plans tailored to the characteristics of the students, while taking into account the principles of mindful learning, meaningful learning, and joyful learning. Deep learning is implemented through student-centered learning that involves discussions, group work, the use of learning media, presentations, and reflection. Factors supporting the implementation of deep learning include school policy support, academic supervision, Teacher Working Group (KKG) activities, training, collaboration among teachers, and the availability of facilities and infrastructure.